Root-specific flavones and critical enzyme genes involved in their synthesis changes due to drought stress on Scutellaria baicalensis - Li, Ping; Ren, Guangxi; Wu, Fei; Chen, Jiaxin; Jiang, Dan; Liu, Chunsheng (Frontiers in Ecology and Evolution, 2023)
Scutellaria baicalensis is rich in bioactive flavonoid, which are widely used in clinical therapy. Many environmental factors, such as water and temperature, affect gene expression and secondary metabolites accumulation in plants. In this study, to explore the effect of drought stress on the accumulation of flavonoids and gene expression in S. baicalensis seedlings, four-week-old Scutellaria baicalensis seedlings were treated with different concentrations of PEG6000 to simulate drought stress. The contents of four root-specific flavones (baicalein, wogonin, baicalin, and wogonoside) in samples under different treatments were quantitatively analyzed by high performance liquid chromatography (HPLC). The expression levels of flavonoid biosynthesis-related genes (PAL1, PAL2, CHS, and UBGAT) were determined by real-time quantitative polymerase chain reaction (qRT-PCR). Also, a correlation analysis between flavonoid contents and gene expression levels was made. The HPLC results revealed that 5% and 10% PEG6000 treatments significantly increased the content of four flavonoids, with 5% PEG 6000 treatment being the most beneficial to the flavonoids accumulation. The qRT-PCR results showed that PAL2 and CHS gene expressions differed significantly in different organs, while PAL1 and UBGAT had poor organ-specific. For genes in roots, the expression of PAL1 and UBGAT was the highest in 5% PEG6000 treatment, and PAL2 and CHS were the highest in 10% PEG6000 treatment. Compared with other concentrations of PEG6000, 5% and 10% PEG6000 were more advantageous for gene expression. Collectively, PEG6000 at a low concentration promoted the accumulation of flavonoids and the expression of related genes. Additionally, the correlation results demonstrated that PAL1, PAL2, CHS, and UBGAT genes in roots stimulated the formation and accumulation of the four flavonoids to varying degrees, while the exception of PAL2 gene expression in roots was negatively correlated with wogonin content. This study for the first time investigated the effect of drought stress on the downstream gene UBGAT in S.baicalensis seedlings as well as the correlation between gene expression and flavonoid content in S. baicalensis seedlings under drought stress, providing a new sight for studying the effects of drought stress on flavonoid accumulation and related gene expression in S. baicalensis.